Multiagent control and predictive diagnostics of distributed iron ore enrichment system based on CPS - Morkun, Volodymyr; Savytskyi, Oleksandr; Tymoshenko, Maxym (Publishing House of Lviv Polytechnic National University, 2016)
The paper presents a description of a distributed control system of processing complex, consisting of three stages with a predictive diagnosis of sensors and actuators. Innovative methods of multi-agent control re focused on as one of the CPS concepts to improve the relation between different stages of enrichment equipment and their coordination.
Keywords: Control Systems; Cyber-Physical Systems; Enrichment; Industry 4.0; Multiagent Control; Predictive Diagnostics